A Model for Power Production Using a Solar-Grid Hybrid System (International Journal of Innovative Research in Engineering & Management, 2021)
Energy is frequently referred to as a country's backbone. The  socioeconomic status of a country can be influenced by  energy use and consumption habits. Most industrial and home  operations are now performed by equipment that runs on  conventional energy as a result of technological  advancements. Thermal power plants are responsible for a  large portion of India's conventional electricity. It has two  consequences: first, it causes pollution, and secondly, it  jeopardises India's energy sector, as the country imports the  great majority of crude oil and coal. One of the most harmful  factors is these power plants. India, with the nation's biggest  national grid network, is frequently unable to supply the  quantity of energy promised, and the system's dependability is  a cause of worry. Solar PV, on either side, is a long-term energy source that  helps to reduce carbon dioxide emissions, despite the fact that  it is weather-dependent and sporadic. Solar PV must be built  with sufficient storage space to be dependable. In solar  technology, a battery bank is typically utilised to store energy.  Batteries are not used since they are harmful to the  environment if discarded and eaten. In this regard, a technology that combines solar PV with the  present grid is discussed in order to provide suitable  alternatives for achieving excellent electricity 24 hours a day,  seven days a week is detailed. The system is designed to get  its electricity from solar PV on bright days, and if there was a  power outage, it may be pulled from the grid. The mechanism  pumps power into the grid when excess power generation  exceeds load demand. The method investigates the impacts of  helps produce and attempts to determine the best model size  and cost. The programme replicates the model to identify  innovative ways to increase integration of renewable energy,  reduce power outages, and preserve the quality of electricity  provided. The suggested plan lays out some of the most  practical and cost-effective strategy for providing a high quality, dependable, and affordable supply of energy for home  use.
Keywords: Grid networks; Conventional; Renewable; Biomass; Batteries; PV systems